Associations among impulsivity, trauma history, and alcohol misuse within a young adult sample. (January 2017) - Bountress, Kaitlin; Adams, Zachary W.; Gilmore, Amanda K.; Amstadter, Ananda B.; Thomas, Suzanne; Danielson, Carla K.
Abstract: Objective: Young adult alcohol misuse is associated with numerous long-term adverse outcomes. Given the link between impulsivity and alcohol use, we examined whether three impulsivity-related traits differentially predicted number of drinks per drinking day (DDD). We also examined whether these effects varied for those with different trauma histories. Method: The current study (n = 254) examined motor, non-planning, and attentional impulsivity as predictors of DDD. It also examined whether impulsivity was differentially predictive of DDD across individuals in: a control group (non-trauma exposed), a trauma exposed but non-PTSD group, and a PTSD group. Results: Regardless of group, more motor impulsivity was associated with more DDD. The effect of non-planning impulsivity varied according to trauma history. Specifically, more non-planning impulsivity predicted more DDD for those without PTSD. Finally, attentional impulsivity was not predictive of DDD. Conclusions: Young adults with high levels of motor impulsivity, regardless of trauma history, may be a particularly high-risk group in terms of propensity for alcohol use/misuse. Additionally, high levels of non-planning impulsivity may signify those at greater risk for alcohol misuse, among those without PTSD. Motor impulsivity and non-planning impulsivity may serve as useful intervention targets in alcohol misuse prevention efforts. Implications for future research in this area are discussed. Highlights: More motor impulsivity was associated with more drinks/drinking day (DDD). The effect of motor impulsivity holds for those with and without trauma and PTSD. More non-planning impulsivity was associated with more DDD. The effect of non-planning impulsivity only held for those without PTSD. There was no association between attentional impulsivity and DDD.